SlPLT6 controls ripening initiation and quality traits through modulation of histone acetylation and methylation in tomato - Xiaoqing He; Yi Wu; Peng Shu; Yanpeng Yin; Heng Deng; Shiyu Ying; Mengbo Wu; Panpan Zhao; Tengbo Huang; Julien Pirrello; Yang Zhang; Don Grierson; et al. (Proceedings of the National Academy of Sciences, 2025)
Improving fruit growth and quality without compromising yield is a highly sought-after goal in crop breeding. Here, we report that an EAR motif-containing transcription factor SlPLT6 controls the onset of fruit ripening and quality traits in tomato. SlPLT6 knockout caused precocious ripening initiation and enhanced fruit qualities without penalizing yield in two tomato cultivars. SlPLT6 represses genes involved in ripening initiation and major quality traits by directly binding to their promoters. Moreover, SlPLT6 connects two repressive mechanisms by recruiting Histone Deacetylase 1 via its C-terminal EAR motif and LIKE HETEROCHROMATIN PROTEIN 1b through the first AP2 domain. Furthermore, Sly-miR159 acts upstream of SlPLT6 to release its repression. Taken together, our data provide insights into the operating mode of SlPLT6 in modulating fruit ripening and quality traits and define a unique gene for targeted crop improvement aimed at upgrading fruit quality without yield penalty.